2018
DOI: 10.1097/scs.0000000000004762
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Opioid Use Among Children, Adolescents, and Young Adults After Common Cleft Operations

Abstract: New persistent opioid use occurs after cleft-related procedures and could lead to chronic use in children, adolescents, and young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 24 publications
5
71
0
Order By: Relevance
“…New persistent use after surgery has been previously described, with rates between 3% and 14%. [13][14][15][16][17]22,23 , high comorbidity, and preoperative mental health and pain disorders, have each been identified in prior studies and were further validated by our findings ( Table 2). We also identified modifiable risk factors for new persistent use, including gastrointestinal complications, surgical approach (eg, thoracotomy), prescription timing, and prescription size.…”
Section: Commentsupporting
confidence: 85%
“…New persistent use after surgery has been previously described, with rates between 3% and 14%. [13][14][15][16][17]22,23 , high comorbidity, and preoperative mental health and pain disorders, have each been identified in prior studies and were further validated by our findings ( Table 2). We also identified modifiable risk factors for new persistent use, including gastrointestinal complications, surgical approach (eg, thoracotomy), prescription timing, and prescription size.…”
Section: Commentsupporting
confidence: 85%
“…We anticipated the alternative outcome definition to be a more inclusive measure of persistent opioid use than our chosen measure of a 90-day opioid supply received in a 12-month period. 21,[35][36][37][38]…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…(After After accounting for the duplicate studies, which appeared under various search headings, 230 distinct articles were identified. The review of the abstracts and/or full texts yielded 17 articles, which evaluated the risk of OUD from opioids administered perioperatively and were therefore retained for further analysis (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The excluded studies pertained to a range of topics including opioid sparing perioperative analgesic techniques, acute opioid tolerance, opioid induced hyperalgesia, perioperative use of ketamine, lidocaine and dexmedetomidine, and multimodal perioperative analgesia.…”
Section: Resultsmentioning
confidence: 99%
“…In eight studies, opioid prescriptions filled within 2 to 4 weeks prior to, and 1 to 2 weeks after the surgery, were considered as perioperative opioids; the prescriptions given preoperatively were included presumably to allow for those filled before the surgery for the perioperative use (9)(10)(11)(12)(13)(14)(15)(16). In six studies, only the pre and postoperative opioid prescriptions were noted, and the exact nature of perioperative opioids was not clear (17)(18)(19)(20)(21)(22). The results, concerned primarily with the opioid prescriptions given for a variable period spanning the time of surgery, typically at the time of hospital discharge, therefore, highlighted mainly the outpatient phase of the perioperative opioid administration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation